Modelos culturais de gestão empresarial: um estudo com valores-modalidade na interface entre linguística cognitiva e antropologia cognitiva - Pierozan, Samanta Kélly Menoncin (My University, 2019)
This thesis is the result of an investigation of cognitive structures and processes, more precisely the ‘cultural model’ theoretical construct, whose theoretical ground creates an interface between Cognitive Linguistics (e.g., LAKOFF, 1987; KÖVECSES, 2005, 2010, 2017; LAKOFF; KÖVECSES, 1987; LAKOFF; JOHNSON, 1980) and Cognitive Anthropology (e.g., BENNARDO; MUNCK, 2014; D’ANDRADE, 1995; D’ANDRADE; STRAUSS, 1992; HOLLAND; QUINN, 1987). Considering that cultural models are presupposed in the worldview, attitudes, behaviors and values of any cultural groups, it aims to reconstruct the dominant cultural model of business management of an industry of the metal-mechanic sector on the analysis of discursive-linguistic manifestations of a sample of individuals. This research presents two basic contributions that support its relevance: (a) to test a theoreticalmethodological design for the research of cultural models and (b) from its results, to offer a way to understand and increase the company management process efficiency, identifying modality-values that guide the dominant cultural model. In this regard, a qualitative-evaluative methodology is adopted in a case study aiming to reconstruct the dominant cultural model through propositions, metaphors, metonymies and its related values. Such reconstruction occurs from data obtained through a descriptive and exploratory theoretical-methodological design proposed that includes: semi-structured interview, transcribed and marked by Conversation Analysis adapted notations; elaboration and application of Likert scale; and also a modalityvaluation scale, proposed by Feltes (2018b). Reading processes are constitutive of the whole methodological device, from the relation between the organizational guidelines reading, fulfilled by the research sample and in the semi-structured interview and Likert scale, as well as by the researcher in her analytical-interpretative procedure of the corpus built from interviews. The main find refers to the current dominant cultural management model of the investigated organization, oriented especially by QUALITYVO, EFFICIENCYVO, UNIONVN+, ADAPTATIONVN+, and COMMUNICATION (person to person)VN, which ones are related to propositions, metaphors and metonymies. These cultural values shared among the sample of participants presents motivational force, since they involve determination of actions in corporate practices. [resumo fornecido pelo autor]
Esta tese é o resultado da investigação sobre estruturas e processos cognitivos, mais precisamente o constructo teórico ‘modelo cultural’, cuja fundamentação teórica cria uma interface entre Linguística Cognitiva (e.g., LAKOFF, 1987; KÖVECSES, 2005, 2010, 2017; LAKOFF; KÖVECSES, 1987; LAKOFF; JOHNSON, 1980) e Antropologia Cognitiva (e.g., BENNARDO; MUNCK, 2014; D’ANDRADE, 1995; D’ANDRADE; STRAUSS, 1992; HOLLAND; QUINN, 1987). Considerando que modelos culturais são pressupostos na visão de mundo, atitudes, comportamentos e valores de quaisquer grupos culturais, objetiva-se reconstruir o modelo cultural dominante de gestão empresarial de uma indústria do setor metalmecânico a partir da análise das manifestações linguístico-discursivas da amostra de sujeitos da pesquisa. Esta pesquisa apresenta duas contribuições básicas que sustentam sua relevância: (a) testar um design teórico-metodológico para a pesquisa de modelos culturais e (b) a partir dos resultados obtidos, oferecer um modo de compreender e eficientizar o processo de gestão da empresa identificando-se quais os valores-modalidade que orientam o modelo cultural dominante. Para tanto, adota-se, em um estudo de caso, uma metodologia qualitativovalorativa que visa à reconstrução do modelo cultural dominante, por meio de proposições, metáforas, metonímias e valores relacionados. Essa reconstrução ocorre a partir de dados obtidos por meio do design teórico-metodológico descritivo-exploratório proposto, que inclui: realização de entrevista semiestruturada, transcrita e marcada por notações adaptadas na Análise da Conversa; elaboração e aplicação de escala tipo Likert; e elaboração e aplicação de uma escala valoração-modalidade, proposta por Feltes (2018b). Processos de leitura são constitutivos de todo o dispositivo metodológico, desde a relação entre a leitura das diretrizes organizacionais, realizada pelos sujeitos da pesquisa e retomada na entrevista semiestruturada e na escala tipo Likert, assim como no procedimento analítico-interpretativo do pesquisador do corpus formado pelas entrevistas. Dos achados, o principal deles remete ao modelo cultural de gestão dominante vigente na organização investigada, o qual é orientado especialmente pelos valores QUALIDADEVO, EFICIÊNCIAVO, UNIÃOVN+, ADAPTAÇÃOVN+, e COMUNICAÇÃO (pessoa a pessoa)VN, os quais estão ligados a proposições, metáforas e metonímias relacionadas. Esses valores culturais mostram-se compartilhados entre os indivíduos participantes da pesquisa, apresentando força motivacional, uma vez que participam na determinação de ações em práticas corporativas. [resumo fornecido pelo autor]
Keywords: Cultura organizacional; Gramática cognitiva; Cognição e cultura; Organizational culture; Cognitive grammar; Cognition and culture